Outcomes of transition from premixed and intensive insulin therapies to insulin aspart/degludec co-formulation in type 2 diabetes mellitus: a real-world experience - GÖZÜ, HÜLYA (TERMEDIA PUBLISHING HOUSE LTD, 2021)
Introduction: To evaluate the efficacy and safety of transition from premixed and intensive insulin to twice-daily insulin degludec/aspart (IDegAsp) co-formulation in patients with type 2 diabetes mellitus. Material and methods: In this 12-week study, patients receiving twice-daily premixed insulin therapy in group 1 (n = 55) were switched to twice-daily IDegAsp. In group 2 (n = 60), patients on intensive insulin therapy were switched to IDegAsp injected twice a day. Inter- and intragroup comparisons were made. Results: A total of 115 patients were included in the study. There was a significant improvement in glycaemic control, median daily total insulin dose, body mass, body mass index, and hypoglycaemic events in group 1 and group 2 with the switch to IDegAsp (p < 0.05). The decrease in median daily total insulin dose requirement in group 2 was higher than that of group 1 (p = 0.001). There was no difference between groups in terms of other parameters (p > 0.05). Conclusions: The current analysis indicates that IDegAsp treatment improves outcomes, with the most notable differences observed in daily total insulin requirement, body mass, and hypoglycaemia.
Keywords: Intensive; degludec; co-formulation; premixed; DEGLUDEC/INSULIN ASPART; GLUCOSE VARIABILITY; PHASE 3A; HYPOGLYCEMIA; TARGET; BASAL; MANAGEMENT; GLARGINE; PEOPLE; ADULTS